2015
DOI: 10.1111/1753-0407.12342
|View full text |Cite
|
Sign up to set email alerts
|

Controlling type 2 diabetes mellitus with herbal medicines: A triple‐blind randomized clinical trial of efficacy and safety

Abstract: There were no significant differences in blood glucose levels, insulin sensitivity or lipid profile among the three groups. However, the use of cinnamon and whortleberry in addition to conventional medical treatment is recommended to adjust weight and blood glucose levels in patients with T2DM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 24 publications
(72 reference statements)
1
59
0
5
Order By: Relevance
“…However, on administration of 50, 150 and 300 mg/kg of ethanolic leaves extracts to the diabetic mice, lipid profile level was found to be restored and turned to words normal level ( Table 4) and results were comparable with results reported earlier by Del et al 7 . Significant reduction in levels of ALT, AST and ALP were found in animals treated with ethanolic leaves extracts ( Table 5).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, on administration of 50, 150 and 300 mg/kg of ethanolic leaves extracts to the diabetic mice, lipid profile level was found to be restored and turned to words normal level ( Table 4) and results were comparable with results reported earlier by Del et al 7 . Significant reduction in levels of ALT, AST and ALP were found in animals treated with ethanolic leaves extracts ( Table 5).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore phytotherapeutics are not alternatives but part of modern medicines. Medical doctor prescribes both synthetic drugs and phytotherapeutics and patients takes medicines to regain their health 7 . The significance of plant based medicines have been increased all over the world and about 50 % medicines available in the markets are made up by plants based active ingredients whose alternative cannot yet be prepared synthetically 8 .…”
mentioning
confidence: 99%
“…The majority of the studies used cinnamon powder in the form of capsule (17 studies) (Akilen et al, ; Aldayel, ; Askari et al, ; Azimi et al, ; Blevins et al, ; Borzoei et al, ; Gupta Jain et al, ; Haghighian et al, ; Hajimonfarednejad et al, ; Mirfeizi et al, ; Nakhaei et al, ; Shishehbor et al, ; Soni & Bhatnagar, ; Torabi et al, ; Vafa et al, ; Wainstein et al, ; Zare et al, ), and the four remaining studies used the cinnamon extract (Anderson et al, ; Talaat & Ammar, ; Weitgasser et al, ; Ziegenfuss et al, ). The 11 trials were conducted in individuals with T2DM (Akilen et al, ; Azimi et al, ; Blevins et al, ; Haghighian et al, ; Mirfeizi et al, ; Soni & Bhatnagar, ; Torabi et al, ; Vafa et al, ; Wainstein et al, ; Weitgasser et al, ; Zare et al, ), and the other trials included women with polycystic ovarian syndrome (PCOS) (three trials) (Borzoei et al, ; Hajimonfarednejad et al, ; Talaat & Ammar, ), participants with overweight (two trials) (Aldayel, ; Nakhaei et al, ), MetS and prediabetes (three trials) (Anderson et al, ; Gupta Jain et al, ; Ziegenfuss et al, ), nonalcoholic fatty liver disease (NAFLD) (one trials) (Askari et al, ), and rheumatoid arthritis (RA) (one trial) (Shishehbor et al, ). In general, the administered dose of cinnamon for these included trials ranged between 336 mg/d of cinnamon extract to 10,000 mg/day of cinnamon powder.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have supported the anti‐obesity effect of cinnamon (Aldayel, ; Gupta Jain et al, ; Mirfeizi et al, ; Zare, Nadjarzadeh, Zarshenas, Shams, & Heydari, ; Ziegenfuss, Hofheins, Mendel, Landis, & Anderson, ), the others have led to conflicting results (Askari, Rashidkhani, & Hekmatdoost, ; Azimi, Ghiasvand, Feizi, Hariri, & Abbasi, ; Talaat & Ammar, ; Wainstein, Stern, Heller, & Boaz, ; Weitgasser et al, ). A recent meta‐analysis indicated that cinnamon might not have a significant impact on body weight, waist circumference (WC), and body mass index (BMI) (Namazi et al, ) in patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…This review includes 11 RCTs 21, 23, 25-27, 33-38 , three of which, Mirfeiz and colleagues 36 , Vafa and colleagues 37 , and Sharma and colleagues 38 had not been included in the meta-analyses noted above. A total of 694 subjects (both placebo and cinnamon treatment) were enrolled across 11 individual RCTs with 15 treatment arms.…”
Section: Studies Included In This Reviewmentioning
confidence: 99%